Phylogeny and Taxonomy on Cryptic Species of Forked Ferns of Asia - Wei, Zuoying; Xia, Zengqiang; Shu, Jiangping; Shang, Hui; Maxwell, Stephen J.; Chen, Lijun; Zhou, Xile; Xi, Wang; Adjie, Bayu; Yuan, Quan; Cao, Jianguo; Yan, Yuehong (Frontiers in Plant Science, 2022)
Cryptic species comprise two or more taxa that are grounded under a single name because they are more-or-less indistinguishable morphologically. These species are potentially important for detailed assessments of biodiversity, but there now appear to be many more cryptic species than previously estimated. One taxonomic group likely to contain many cryptic species is Dicranopteris, a genus of forked ferns that occurs commonly along roadsides in Asia. The genus has a complex taxonomical history, and D. linearis has been particularly challenging with many intra-specific taxa dubiously erected to accommodate morphological variation that lacks clear discontinuities. To resolve species boundaries within Dicranopteris, we applied a molecular phylogenetic approach as complementary to morphology. Specifically, we used five chloroplast gene regions (rbcL, atpB, rps4, matK, and trnL-trnF) to generate a well-resolved phylogeny based on 37 samples representing 15 taxa of Dicranopteris, spanning the major distributional area in Asia. Our results showed that D. linearis are polyphyletic, suggesting cryptic diversity within the species. Thus, based on these results, we erected Dicranopteris austrosinensis Y.H. Yan & Z.Y. Wei sp. nov. and Dicranopteris baliensis Y.H. Yan & Z.Y. Wei sp. nov. as distinct species. We also inferred that the extant diversity of the genus Dicranopteris may result from relatively recent diversification in the Miocene based on divergence time dating. Our study not only resolves several previously unsettled aspects of species classification of Dicranopteris, including six new combinations, but also provides an example of integrating molecular and morphological approaches to elucidate cryptic diversity in taxonomically difficult groups.